Counselling Attitudes and Skills for Handling HIV and AIDS Clients in Hospitals in Anambra State - Uju. P. , Egenti, P. Uju. Egenti, (African Journal of Education,Science and Technology (AJEST), 2016)
The purpose of this study was to investigate the counselling attitudes and skills for handling HIV and AIDS clients in government and mission hospitals in Anambra State. Two research questions and two hypotheses guided the study. The study adopted a descriptive research design. The population of the study comprised 29 HIV and AIDS counselling personnel in the hospitals with Heart-to-Heart Centres in Anambra State. All respondents were studied, so there was no need for sample and sampling technique. The study used 59 structured questionnaire items to obtain data to answer the research questions. Mean scores were used to answer the research questions while t-test was used to test the hypotheses at 0.05 level of significance. The findings indicated that the HIV and AIDS counselling personnel in the area of the study possess good counselling attitudes but they have low knowledge of HIV and AIDS counselling skills. Further findings show that the HIV and AIDS counselling personnel in the area of the study are competent in the exhibition of counsellor attitudes but are incompetent in the knowledge of counselling skills. In the strength of the above, it was recommended that the counselling personnel in the State can improve their knowledge of counselling skills by attending conferences, seminars and workshops. They should improve their knowledge of counselling skills through research and reading of current counselling books. Again, the state agency for the control of HIV and AIDS should liaise with donor agencies for the procurement and distribution of current counselling books and kits to the counselling personnel in the hospitals to enable them improve their knowledge. Many counselling skills exist in literature and they can always reach them through research or reading current counselling books